Terapi Seni Melalui Melukis pada Pasien Skizofrenia dan Ketergantungan Narkoba - Sarie Rahma Anoviyanti (ITB Journal Publisher, LPPM ITB, 2008)
For centuries, human used various forms and/or elements of art as an effort to 'treat' their body and souls. The ancient Greece used the existence of theatrical art as something that has catharsis effect in